Pengaruh Budaya Organisasi Dan Karakteristik Individu Terhadap Motivasi dan Kinerja Karyawan Pada PT Perkebunan Nusantara XII Kantor Wilayah I Jember - Iqbal Hadi Nurisman; Diana Sulianti T; M. Syaharudin (UPT Penerbitan Universitas Jember, 2017)
This research aims to examine the effect of organitation culture on motivation, individual characteristics on motivation,organitation culture on performance of employees, individual characteristics on performance of employees, and motivation onperformance of employees in PT. Perkebunan Nusantara XII Regional Office I Jember . The population in this research is allemployees of PT. Perkebunan Nusantara XII Regional Office I Jember. The sampling method used was sensus method.withrespondent total as many as 37 people. Variables used as many as four variables; organizational culture, individualcharacteristics, motivation, and performance of employees. The analysis tool used is the path analysis (path analysis). Theresults showed that: 1) There is influence of organizational culture on motivation in PT. Perkebunan Nusantara XII RegionalOffice I Jember; 2) There is influence of individual characteristic on employees motivation in PT. Perkebunan Nusantara XIIRegional Office I Jember; 3) There is influence of organizational culture on performance of employees in PT. PerkebunanNusantara XII Regional Office I Jember; 4) There is effect of individual characteristics on employees performance PT.Perkebunan Nusantara XII Regional Office I Jember; and 5) There is effect of motivation on performance of employees PT.Perkebunan Nusantara XII Regional Office I Jember.